Mitochondria Homeostasis and Oxidant/Antioxidant Balance in Skeletal Muscle-Do Myokines Play a Role? - Brian Pak Shing Pang; Wing Suen Chan; Chi Bun Chan (MDPI AG, 2021)
Mitochondria are the cellular powerhouses that generate adenosine triphosphate (ATP) to substantiate various biochemical activities. Instead of being a static intracellular structure, they are dynamic organelles that perform constant structural and functional remodeling in response to different metabolic stresses. In situations that require a high ATP supply, new mitochondria are assembled (mitochondrial biogenesis) or formed by fusing the existing mitochondria (mitochondrial fusion) to maximize the oxidative capacity. On the other hand, nutrient overload may produce detrimental metabolites such as reactive oxidative species (ROS) that wreck the organelle, leading to the split of damaged mitochondria (mitofission) for clearance (mitophagy). These vital processes are tightly regulated by a sophisticated quality control system involving energy sensing, intracellular membrane interaction, autophagy, and proteasomal degradation to optimize the number of healthy mitochondria. The effective mitochondrial surveillance is particularly important to skeletal muscle fitness because of its large tissue mass as well as its high metabolic activities for supporting the intensive myofiber contractility. Indeed, the failure of the mitochondrial quality control system in skeletal muscle is associated with diseases such as insulin resistance, aging, and muscle wasting. While the mitochondrial dynamics in cells are believed to be intrinsically controlled by the energy content and nutrient availability, other upstream regulators such as hormonal signals from distal organs or factors generated by the muscle itself may also play a critical role. It is now clear that skeletal muscle actively participates in systemic energy homeostasis via producing hundreds of myokines. Acting either as autocrine/paracrine or circulating hormones to crosstalk with other organs, these secretory myokines regulate a large number of physiological activities including insulin sensitivity, fuel utilization, cell differentiation, and appetite behavior. In this article, we will review the mechanism of myokines in mitochondrial quality control and ROS balance, and discuss their translational potential.